Adolescent women's assertiveness of their reproductive rights in relation to their locus of control. - Imbang, Lei Marie F.
The study was undertaken to determine relationship that could exist between the adolescents' locus of control and reproductive rights assertiveness. Specifically, it aims to answer the following questions: 1.) What is the distribution of the locus of control (internal to external) of adolescents? 2.) What is the distribution of the level of reproductive rights assertiveness of adolescent women? 3.)What possible relationship could exist between the adolescent women's locus of control and reproductive rights assertiveness? 4.)Which among the components of Reproductive rights are adolescent women most assertive of? Which among the components are they least assertive of?, Eighty college women from four different universities served as the respondents of the study. Two sets of questionnaires (the Reproductive Rights Assertive Scale and the Locus of Control Scale) were administered to the respondents and their scores on these two scales were correlated to find out the possible relationship that could exist between Locus of Control and Reproductive Rights Assertiveness. The study had the following findings: 1) The number of respondents with internal locus of control. 2.) The range obtained scores of the respondents in the Reproductive Rights Assertiveness Scale indicates that respondents fall between being moderately assertive to highly assertive. 3.) There exists a relationship between respondents' locus of control and Reproductive Rights Assertiveness (r=-0.225 exceeds r crit = +- 0.183 at 0.05 alpha level). Locus of Control and Assertiveness of Reproductive Rights are negatively correlated. A low score in the LOC Scale is associated with high Reproductive Rights Assertiveness. This means that a low level of Reproductive Rights Assertiveness is associated to external locus of control. A high level of Reproductive Rights Assertiveness is associated with internal locus control. 4.)Respondents' scores in the right to health component of their Reproductive Rights are higher than their scores in the right to manage one's sexuality component (t=-exceeds t crit = +-1.667 at 0.05 alpha level). Respondents are more assertive in the right to health component than the right to manage one's sexuality component.